PERANCANGAN SISTEM KEAMANAN SEPEDA DI TEMPAT UMUM BERBASIS RFID - Purhendi Bayu Basuki; Unang Sunarya; Atik Novianti (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2017)
Most of the bicycle par king sistems in open areas today still use the traditional method of using only a piece of paper provided by the parking attendants and in the open area without a guardrail so that the sense is still minimal supervision. Lack of efficiency of the parking p rocess so prone to cheating and crime theft becomes a weakness of the parking sistem in this open area. To solve the above problem then created a security sistem where bike parking by using RFID technology (Radio Frequency Identification). RFID itself is a method of data communication by using a predetermined frequency to exchange data within a certain distance. To implement this bike security sistem using RFID sensors are controlled using Arduino Uno. The hardware used this parking sistem tool will be plac ed inside the box design mechanical bicycle rack made. The conclusion that can be drawn from making this research is the error rate of reading and RFID identification is 0%. Based on the test results, the maximum detection distance RFID tag customer agains t RFID reader is 4 cm. Overall, this bike safety sistem can be implemented as a prototype that has the potential to be developed and become an alternative solution for bicycle safety.